Penentuan Energi Kisi Oksida-Oksida Piroklor - Dede Suhendar; Ismunandar Ismunandar (Jurnal Matematika & Sains, 2006)
Lattice energy of pyrochlore oxides prediction is important in relation with the synthesis effort. This work was aimed to find an equation that could be used to predict the lattice enthalpy of pyrochlore oxides. As standards, pyrochlores with known enthalpy formation were used to calculate the lattice entalphy via Born Haber cycle U(BHC). Lattice energies, U, of pyrochlore oxides were calculated by Glasser (G), Glasser-Jenkins, (GJ), and Yoder-Flora, (YF) equations. Plotting of Born-Haber lattice energies U(BHC) vs. U(G), U(GJ), and U(YF) resulted in R2 = 0.9564, 0.8671, and 0.9993, respectively. Based on the fitting of U(BHC) vs. U(YF), then a combination of Yoder-Flora and Kapustinskii equations were formulated and tested for U(BHC) of pyrochlore oxides. The Yoder-Flora-Kapustinskii (YFK) equation was U(YFK)pyrochlore = Î£ U(K) oxide of A + Î£ U (K) oxide of B where U(K) is lattice energy of oxide calculated by Kapustinskii equation using ionic radii of A in eight coordination number, and B in six coordination number, except for B ions from oxide fluorite structures in eight coordination number. The differences between U(YFK) and U(BHC) were < 3 %..